A calculation of radio electronic devices own noises in the range of low frequencies - Kolodiy, Zenoviy; Nedostup, Leonid; Kolodiy, Andriy (Видавництво Львівської політехніки, 2010)
Formula for calculation of own noises level of radio electronic devices in the range of low frequencies.
Keywords: flicker-noise; spectral power density; relaxation time of system.